Time-resolved quantitative inter-eye comparison of cardiac cycle-induced blood volume changes in the human retina - Tornow, Ralf-Peter; Odstrcilik, Jan; Kolar, Radim (Biomedical optics express, 2018)
We describe a low-cost, easy to use binocular instrument to acquire retinal video sequences of both eyes simultaneously. After image registration, cardiac cycle-induced pulsatile light attenuation changes can be measured quantitatively with high spatial and temporal resolution. Parameters such as amplitude, pulse form, and time shift between light attenuation changes can be calculated and compared between eye sides. Deviation from inter-eye symmetry can be not only an early sign of beginning eye diseases such as glaucoma but also a sign of pathological changes in the carotid arteries; hence, this method can improve the early detection of pathological changes. Important features compared to existing monocular instruments are a narrow band light source with the wavelength close to the peak of the blood extinction, and a proportional relationship of image intensity and light intensity, which are the main requirements for quantitative evaluation.